2023
DOI: 10.1039/d2fo03722j
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of exposure to β-carboline heterocyclic amines: insight into metabolic perturbations and biochemical analysis

Abstract: As a class of bioactive and toxic compounds widely present in foodstuff, the health effects of dietary exposure to β-carboline heterocyclic amines (HAs) have not been elucidated. Based on our...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Given that WDP food groups are primarily subjected to high-temperature methods like frying and baking, it is possible that the association between WDP and mental health risk is linked to the formation of detrimental substances during the Maillard reaction. These substances include advanced glycation end products (AGEs), heterocyclic amines, and acrylamide [ 75 , 76 ]. Since, our previous studies have confirmed that those harmful compounds could be promoting oxidative stress and neuroinflammation through the blood–brain barrier, which consequently leads to neurocognitive deficiencies that closely resemble those documented in individuals experiencing major depressive disorder [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that WDP food groups are primarily subjected to high-temperature methods like frying and baking, it is possible that the association between WDP and mental health risk is linked to the formation of detrimental substances during the Maillard reaction. These substances include advanced glycation end products (AGEs), heterocyclic amines, and acrylamide [ 75 , 76 ]. Since, our previous studies have confirmed that those harmful compounds could be promoting oxidative stress and neuroinflammation through the blood–brain barrier, which consequently leads to neurocognitive deficiencies that closely resemble those documented in individuals experiencing major depressive disorder [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%